“Determinación de la época de corte del pasto Toledo (Brachiriabrizantha) mediante la cuantificación de proteínas en la hoja” - Sánchez Vélez, Edison Vicente (2018)
VII. SUMMARY The present experimental work was carried out on the grounds of the Experimental Farm "San Pablo" belonging to the Faculty of Agricultural Sciences of the Technical University of Babahoyo, located at Km 7 ½ of the Babahoyo - Montalvo road. The area is tropical wet, according to the Holdribge classification, with an average annual temperature of 24.7 ° C, an average annual precipitation of 1500.7 mm, relative humidity of 85.5%, vapor tension 25.9 Mb, dew point 22.5 ° C and an evaporation of 639.8 mm. Heliofaniawouldsay 3.5 Hl (light hours). 1 / The geographic coordinates are west longitude 277438.26 UTM, south latitude 110597.97 UTM and altitude of 8 masl. The genetic material used was seeds of Toledo improved grass (Brachiariabrizantha), it was obtained from a commercial house of recognized trajectory. The proposed objectives were to determine the concentration of proteins as a cut indicator of the Toledo grass (Brachiariabrizantha) for cattle feed in the Babahoyo area; determine the concentration of proteins in the leaves of the Toledo grass in the cutting season; establish the percentage of proteins and the volume of biomass generated most suitable for bovine feeding; identify the best age cut height of the Toledo grass (Brachiariabrizantha), in relation to the production in the study area. The treatments studied were cutting ages at 70, 80, 90 and 100 days after sowing at a height of 20 cm, with application of sulfur and magnesium in the treatments specified in the attached treatment chart. The experimental design used was Random Blocks in factorial arrangement of A x B, with twelve treatments and three repetitions. For comparison and adjustments of means of treatments, the Tukey test was used at 95% of probabilities. For the development of the trial, agricultural work was carried out, such as soil preparation, sowing, irrigation, weed control, fertilization and control of pests and diseases. The evaluated data were plant height, leaf / stem ratio, stem number, number of leaves per plant, production of green forage biomass (MV) per hectare, production of dry matter (MV) per hectare and leaf analysis to know protein. The results obtained were determined that with 30 kg / ha S + 30 kg / ha Mg and 30 kg / ha S + 0 kg / ha Mg, greater significance was obtained and the cut-off time with the highest height was 100 days after of the sowing; Fertilizer doses of 30 kg / ha S + 30 kg / ha Mg and 30 kg / ha S + 0 kg / ha Mg had more leaves statistically. The cut-off time 100 days after sowing was statistically superior. Apply 30 kg / ha S + 30 kg / ha Mg and 30 kg / ha S + 0 kg / ha Mg, generate more stems. The cutting season 100 days after sowing gave more stems. When fertilizers were not applied, there was greater value in the leaf / stem ratio. The cutting season 70 days after sowing had a greater relationship. More green and dry biomass was produced applying 30 kg / ha S + 30 kg / ha Mg (21488.33 kg / ha) and 30 kg / ha S + 0 kg / ha Mg. With the cut-off time 100 days after sowing, more biomass was produced. There was a greater accumulation of protein in the leaves when fertilized with 30 kg / ha S + 0 kg / ha Mg. Higher protein generation occurred in the cuts 70 days after sowing and 80 days. Key words: Brizantha, cultivars, biomass production, protein content, growth rate, age, cutting season.